African personhood and applied ethics - Molefe, Motsamai (African humanities series., 2020)
Recently, the salient idea of personhood in the tradition of African philosophy has been objected to on various grounds. Two such objections stand out -- the book deals with a lot more. The first criticism is that the idea of personhood is patriarchal insofar as it elevates the status of men and marginalises women in society. The second criticism observes that the idea of personhood is characterised by speciesism. The essence of these concerns is that personhood fails to embody a robust moral-political view. African Personhood and Applied Ethics offers a philosophical explication of the ethics of personhood to give reasons why we should take it seriously as an African moral perspective that can contribute to global moral-political issues. The book points to the two facets that constitute the ethics of personhood -- an account of (1) moral perfection and (2) dignity. It then draws on the under-explored view of dignity qua the capacity for sympathy inherent in the moral idea of personhood to offer a unified account of selected themes in applied ethics, specifically women, animal and development.